Enhanced bioethanol fermentation from mixed xylose and glucose using free and immobilized cultures: mathematical model and experimental observation - Ghods, Nosaibeh Nosrati (Centre for Bioprocess Engineering Research, 2019)
Bioethanol plays a significant role in the world of liquid biofuel. However, majority of bioethanol is produced from edible food crops such as corn and sugarcane that causes an increase in demand for vacant lands for food production and, subsequently, increase in the cost of food manufacturing. Therefore, alternative raw materials for bioethanol production are sought after, such as sugarcane bagasse which is a waste material from the sugar industry. South Africa, a net sugar exporter, has a large potential to produce bioethanol from sugarcane bagasse. This research focuses on the study of the production of bioethanol from glucose and xylose which are the two most abundant sugars in hydrolysed sugarcane bagasse. To date, no suitable wild type organisms can concomitantly ferment both glucose and xylose to ethanol efficiently. Options to address the co-fermentation of glucose and xylose include genetic modification of the selected microorganism to include both pathways - limitation in the understanding of the metabolic pathways regulations - or utilization of two microorganisms in co-culture or sequential culture e.g. Zymomonas mobilis and Pichia stipitis for efficient fermentation of glucose and xylose respectively. In this study, the dual micro-organism route is explored. There are numerous problems associated with co-culturing. Xylose, a non-preferred carbon source is only converted if the glucose concentration is adequately low due to catabolite repression. In order to increase xylose conversion, a low glucose concentration is required. Therefore, two stage sequential fermentation either in one or two reactors was tested. A high inoculum of suspended or immobilized Z. mobilis was inoculated in the first stage to convert the glucose rapidly. Varying reactor configuration, including the continuous fluidized bed, continuous stirred tank reactor (CSTR) and stirred batch reactor were considered. The products and residual substrate from this fermentation was then directed to a second stage, using either a CSTR or stirred batch configuration, with a high inoculum of P. stipitis in suspension culture for conversion of xylose. When immobilized, Z. mobilis was entrapped in calcium alginate beads. On the issue of ethanol tolerance, P. stipitis is generally more easily inhibited by ethanol (threshold ethanol concentration of 35 g L-1) compared to other ethanol producing strains such as Z. mobilis (threshold ethanol concentration of 127 g L-1) and Saccharomyces cerevisiae (threshold ethanol concentration of 118.2 g L-1). In order to overcome this, a continuous bioprocess was investigated to keep ethanol concentrations in Stage II below 35 g L-1 to prevent inhibition of metabolic reactions in P. stipitis. Further, ethanol fermentation by Z. mobilis requires obligate anaerobic conditions while xylose conversion by P. stipitis is optimum under microaerobic conditions. Therefore, oxygen was sparged into the second P. stipitis stage only. The following components were carried out in this project to improve the kinetic model and to find accurate kinetic data in the selected process of the two stage sequential fermentation. Firstly, where kinetic parameters were not available in literature, the kinetic parameter relationships of glucose and xylose utilization between different constructs of the same species were examined, for example, a wild type and engineered strain. This approach was used for glucose conversion using wild type Z. mobilis, owing to the ill-fit of available kinetic parameters with experimental results. In this study, the correction factors on estimated kinetic parameters from linear and non-linear regression when a xylose fermentation route was inserted recombinantly (S. cerevisiae RWB 217) into the native culture (S. cerevisiae CEN.PK 113-7D) were determined. From kinetic parameters of an engineered strain with the xylose-fermenting pathway (Z. mobilis ZM4 (pZB5)) and the correction factors, kinetic parameters of the wild-type Z. mobilis ZM4 were determined. Predicted rates of Z. mobilis ZM4 were then validated with experimental data generated in this study. Then, the optimum initial biomass concentration required to provide a faster volumetric rate of sugar utilisation and ethanol production, as well as the optimum oxygenation level for xylose conversion using P. stipitis achieved through appropriate aeration were investigated through experimental observation and using a MATLAB mathematical model developed through combination of the Andrews and Levenspiel's models, with oxygen, substrate, cell and product terms. Experiments were carried out to validate the kinetic model and data under anaerobic and microaerobic growth conditions in a batch process. The results showed that both increasing the initial biomass concentration (3 g L-1) and operating under optimum oxygenation levels (0.1 vvm) benefitted the ethanol production and yield by P. stipitis from xylose. It was also concluded that the addition of the oxygen effective factors in the developed model allowed for optimization of aeration in the fermentation system. Next, the custom kinetic model for fermentation process of bioethanol production was developed in Aspen Custom Modeller (ACM) and embedded in Aspen Plus. The model includes equations of vapour-liquid equilibrium (VLE), mass balance, and energy balance (e.g. molecular weight, thermodynamic phase equilibria, kinetic equation). The obtained results showed better agreement between industrial data and kinetic model (1% differences) than a stoichiometric model (9% differences). The simulation showed that ACM integrated into Aspen Plus allowed for complex biological processes to be accurately predicted for biomass growth, ethanol production and sugar consumption. Finding suitable microorganisms and process conditions for efficient glucose and xylose conversion is still currently a challenge and requires optimization. Therefore, this research focusses on improving the conversion of glucose and xylose to bioethanol, with specific emphasis on the fermentation systems used to maximize biomass efficiency, and ethanol yields and productivities. Manipulation of process conditions ranging from operation conditions (e.g. batch, fed-batch, continuous), process parameters (aeration, temperature, pH), immobilization technique and type of microorganism initially using kinetic models and thereafter validating with experimental data, therefore, offers a quick and strong foundation in improving bioethanol yields and productivities.